2020
DOI: 10.3856/vol48-issue4-fulltext-2503
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of near-surface zooplankton community structure in the southern Gulf of Mexico

Abstract: The zooplankton taxonomic group composition was analyzed in a known spawning area for snooks of the family Centropomidae during March 2011-February 2012 near the González River's mouth, a tributary of the Grijalva-Usumacinta River system, discharging into the southern Gulf of Mexico. Zooplankton was collected near the surface using three distinct zooplankton nets (20, 64, and 120 μm). Sixteen zooplankton taxonomic groups were collected between the three nets. Copepoda (76.9%), Trematoda (6.7%), Bivalvia (4.6%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Notably, this abundance pattern is consistent with previous studies addressing zooplankton community composition through the morphological identification of taxa in the same region of the GoM. For example, Cruz‐Rosado et al (2020) reported that the abundance of certain taxa, such as Copepoda, Trematoda, Bivalvia, and Chaetognatha, increased with higher sea surface temperatures. Moreover, Espinosa‐Fuentes et al (2009) highlighted that zooplanktonic biomass and ichthyoplankton density may be also influenced by temperature variations in the water column.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Notably, this abundance pattern is consistent with previous studies addressing zooplankton community composition through the morphological identification of taxa in the same region of the GoM. For example, Cruz‐Rosado et al (2020) reported that the abundance of certain taxa, such as Copepoda, Trematoda, Bivalvia, and Chaetognatha, increased with higher sea surface temperatures. Moreover, Espinosa‐Fuentes et al (2009) highlighted that zooplanktonic biomass and ichthyoplankton density may be also influenced by temperature variations in the water column.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, due to their small size, limited capacity for self‐dispersal, and high sensitivity to environmental change, zooplankton are also useful bioindicators when evaluating the health of marine ecosystems (Buttay et al, 2015; Johnston et al, 2015; Parmar et al, 2016; Yang & Zhang, 2019). Environmental change and ecological processes shape zooplankton communities, both in terms of their spatial and temporal abundance (Färber Lorda et al, 2019; Shropshire et al, 2020) and taxonomic composition (Buttay et al, 2015; Cruz‐Rosado et al, 2020), and may lead to the loss of zooplankton biodiversity (Gazonato Neto et al, 2014; Parmar et al, 2016), which can affect ecosystem services and result in economic consequences (Beaugrand et al, 2010; Bucklin et al, 2016; Everaert et al, 2018; Johnston et al, 2015).…”
Section: Introductionmentioning
confidence: 99%